The cellular and molecular mechanisms underlying apoptosis augmentation via cell cycle arrest in human carcinoma HCT116 cells by Swietenia macrophylla King derived phytochemicals / Goh Bey Hing - Goh, Bey Hing (2012)
Swietenia macrophylla King is a large mahogany tree growing in the rainforest of Malaysia. Its seeds have been widely used in traditional medicine to treat various diseases. In this study, anticancer properties of Swietenia macrophylla were examined for the first time. Solvent extraction yielded crude ethanolic extract (SMCE) which exhibited prominent bioactivites towards various cancer cell lines namely, MCF-7, KB, HepG2, CasKi and HCT116. Thus, SMCE was fractionated into hexane (SMHF), ethyl acetate (SMEAF) and water fraction (SMWF) for further cytotoxic evaluation. The SMEAF was found to be most potent in inhibiting the growth of human colorectal carcinoma cell line (HCT116) yielding an IC50 of 35.35 μg/ml. SMEAF was found to induce oxidative stress in HCT116 as the treated cells demonstrated increased intracellular ROS level. Inversely, intracellular total glutathione level was lowered. The following experiments suggested apoptosis induction in treated cells, as was reflected by aberrant nuclear changes, sub-G1 cells, disruption of mitochondrial membrane potential, externalization of phosphatidylserine along with activation of the caspase -3/7 and -9. Besides, exposure to SMEAF increased expression level of Bax but not Bcl-2 in HCT116 cells. These results suggested that the treatment with SMEAF may have led the cells to undergo oxidative stress and followed with apoptosis through the intrinsic pathway. Meanwhile, cell cycle analysis in treated cells showed dose-dependent increase in G1 phase population. PCNA Q-PCR analysis confirmed the slowing down of cell replication process upon treatment. The decrease in various cyclin-dependent kinases encoding genes along with the increase in cyclin-dependent kinase inhibitor 1 (p21) and p53 suggested that the arrest of cells might be activated through p53-dependent pathway. ii Chemical characterization of fractionated SMEAF by using GC-MS enables identification of the presence of chemical constituents. Compound isolation and structural elucidation of the bioactive SMEAF yielded eight compounds which were mostly limonoids, namely, 3,6-O,O-Diacetylswietenolide (1), Swietenine (2), 3-O-Tigloylswietenolide (3), Swietenolide (4), Hexadecanoic acid (5), Proceranolide (6), Khayasin T (7) and 6-O-acetylswietenolide (8). Some of the named chemicals (3, 5, 6, 7) were shown to possess cytotoxic effect. Among them, compounds 5, 6, 7 were known apoptotic inducers; the amount of compound 3 was insufficient for in-depth studies. Thus, the focus was shifted to swietenine, a known hypoglycemic inducing agent which shares the same functional groups with compound 3. Chemical modification was performed on swietenine to obtain its derivative that is able to dissolve in aqueous condition for further biological evaluations. The swietenine derivative, namely swietenine acetate was found to inhibit the growth of HCT116 cell line. This investigation revealed the ability of swietenine acetate to cause apoptosis and arrest of cells. These observed effects were further confirmed using numerous molecular biological techniques. Interestingly, the viable cell population detected in Annexin V/PI did not show further reduction in viability after prolonged exposure to swietenine acetate. This was accompanied by HSP70 protein elevation in swietenine acetate treated cells, which may be responsible for apoptosis impediment in HCT116. Conclusively, these finding suggested limonoids present in S. macrophylla was associated with apoptotic induction in cancer cells. This provides the scientific evidence for the possible use of limonoids derived from S. macrophylla for chemoprevention.